Pengaruh Konten Viral di Media Sosial Terhadap Penyelesaian Kasus Penganiayaan : oleh Satreskrim Polres Kolaka Polda Sulawesi Tenggara - Pradana, Akbar Reno Adhi; Rusmawan, Teddy (Brand Communication, 2025)
This study aims to determine whether there is an influence of viral news on social media on the settlement of criminal cases, especially persecution by the Kolaka Police satreskrim. The theoretical study uses uses and gratification theory with a focus on variables, namely viral content on social media (independent variable) and case resolution (dependent variable). The research used a survey model on 37 police officers who handled the case, as well as the public as many as 100 respondents. Quantitative data processing with a simple linear regression model. The results showed that there was a weak influence of viral reporting of persecution cases from the community side by 26.4%. In contrast to that, from the side of police officers, the survey showed a very small influence of only 1.6%. Thus viral news of persecution cases will not increase the resolution of criminal cases in existing law enforcement.